Формування електронних інформаційних ресурсів сільських бібліотек: сучасні тенденції, проблеми та перспективи - Панчишин, Наталія; Марковець, Олександр (Видавництво Львівської політехніки, 2017)
The present thesis deals with the peculiarities of forming electronic information resources in rural libraries. It is focused on main problems of forming the electronic information resources in libraries. The characteristics and advantages of digital libraries are listed.
Keywords: бібліотека; інформаційне суспільство; формування інформаційного ресурсу; бібліотечно-інформаційний ресурс